Students’ perception and self-efficacy in blended learning of medical nutrition course: a mixed-method research - Aksara Regmi; Xuanxia Mao; Qi Qi; Wenjing Tang; Kefeng Yang (BMC Medical Education)
Abstract Background The blended teaching mode, which combines online and offline learning, has gained significant traction in higher education. This study aims to explore the impact of blended learning on students’ academic performance, engagement, and self-efficacy in a medical nutrition course. Methods A mixed-method research design was employed, involving 110 undergraduate students enrolled in a blended learning medical nutrition course and a control group of 93 students from a traditional learning environment. Data collection included academic performance assessments, semi-structured interviews, and an anonymous questionnaire. Quantitative data were analyzed using t-tests and chi-square tests, while qualitative data were subjected to thematic analysis. Results Students in the blended learning group demonstrated significantly higher self-efficacy, particularly in organizing their study plans, participating in interactive learning activities, and applying course knowledge. Academic performance was notably better in collaborative assessments, such as group discussions and exploratory projects, in the blended learning group compared to the control group. Qualitative analysis revealed that students appreciated the flexibility and engagement offered by the blended learning model, although they also faced challenges related to self-discipline and the learning environment. Conclusions The blended learning approach enhances student engagement, self-efficacy, and collaborative skills, particularly in group-based assessments. While students benefit from the flexibility and richness of learning resources, challenges related to self-discipline and learning environments need to be addressed to optimize the effectiveness of blended learning.